2015
DOI: 10.1177/1203475415581311
|View full text |Cite
|
Sign up to set email alerts
|

Autologous, Noncultured Epidermal Cell Suspension Grafting in the Management of Mechanically and Chemically Induced Leukodermic Scars

Abstract: In this small case series, lack of fluorescence in leukodermic scars may be a useful negative prognostic indicator for MKTP, but additional trials are needed to verify that this is not due to melanocompetency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Another RCT assessed the approach of combination split‐thickness autografts with harvested skin cell suspension and the split‐thickness autograft alone for chronic wound treatment, which demonstrated that complementary split‐thickness autologous skin grafting with autologous skin cells harvested using ReCell technology improved the healing rate of chronic wounds . Meanwhile, ReCell technology in combination with other technologies, such as lipofilling subdermal reconstruction, CO 2 laser ablation, surgical excision, or medical needling appeared to be effective methods to correct injured sequelae including hypopigmentation and scar in skin cancer or burns even in congenital melanocytic nevi …”
Section: Resultsmentioning
confidence: 99%
“…Another RCT assessed the approach of combination split‐thickness autografts with harvested skin cell suspension and the split‐thickness autograft alone for chronic wound treatment, which demonstrated that complementary split‐thickness autologous skin grafting with autologous skin cells harvested using ReCell technology improved the healing rate of chronic wounds . Meanwhile, ReCell technology in combination with other technologies, such as lipofilling subdermal reconstruction, CO 2 laser ablation, surgical excision, or medical needling appeared to be effective methods to correct injured sequelae including hypopigmentation and scar in skin cancer or burns even in congenital melanocytic nevi …”
Section: Resultsmentioning
confidence: 99%
“…In a recent literature review, Madu et al 2 . list many treatments for postinflammatory hypopigmentation, including the laser hole technique using nonfractional CO 2 laser, 35 fractional CO 2 laser, 1,36 fractional CO 2 laser with topical latanoprost, 1,36 1,550‐nm fractional laser with or without topical bimatoprost 36 or with topical tretinoin or pimecrolimus, 37 skin grafting, 36,38–40 needling and noncultured autologous skin cell transplantation, 41 needling and UVA, 42 excimer laser, 43–45 dermabrasion, 39 cosmetic camouflage, 46 and cosmetic tattooing 47 . Laser treatments 37 and microneedling 41 can induce repigmentation by collagen remodeling 37,48 .…”
Section: Discussionmentioning
confidence: 99%
“…The amount, type, and distribution of the dark biopolymer melanin in the skin contribute to the uniqueness of every person [1,2]. Already after deep-partial thickness-burn trauma, therapy results can include postburn hypopigmentation (leucoderma) [3][4][5]. Visual impressions of body form and skin color are important factors for interactions among humans, especially for facial appearance.…”
Section: Introductionmentioning
confidence: 99%